The old man & the gun [videorecording (DVD)] - Lowery, David; Affleck, Casey, 1975-; Glover, Danny; Sumpter, Tika; Carradine, Keith, 1949-; Spacek, Sissy; Grann, David (Twentieth Century Fox Home Entertainment, 2019)
At age 70, Forrest Tucker infamously made his escape from the tough San Quentin prison. Once he had gained his freedom, he embarked on a new set of heists that left investigators scratching their heads and the public fascinated by the story. This true story details Tucker's life which includes a detective wrapped up in the case, and a female who takes a liking to Tucker despite the criminal path he's on.